Mode of Production : The Final Horizon of Practice and Theory - Heller, Henry (Historical Materialism Book Series, 2026)
Mode of Production: The Final Horizon of Practice and Theory re-invigorates the Marxist concept 'mode of production' by showing how it continues to have a central place in understanding the broad sweep of human history, while also offering crucial resources to inform social justice activism today. Drawing on recent materialist theory and newer insights from historical and anthropological scholarship, the book discusses the three modes of production that existed, the conflicts between them, the importance of Indigenous struggles to socialism, and explicates a materialist contemporary cultural politics. The book offers a pathway for activism and theory through the wide range of contemporary hegemonies.